Branding the Surabaya Wonorejo Mangrove Botanical Garden Tourism, Through Social Media Video Content - Bayu Setiawan; Ririn Puspita Tutiasri; Jimmy Putra Pradana (Nusantara Science and Technology Proceedings, 2023)
Tourism Branding is an activity to introduce a tourist spot to the public. One of the tourism branding activities is by creating advertising videos that are packaged attractively, so that they can attract people to visit. Many tourist attractions are empty of visitors after the Covid-19 pandemic, because there is a ban on gathering in certain places. This makes many tourist attractions empty of visitors, one of which is the Surabaya Wonorejo mangrove botanical garden. Community Service Activities, UPN Serves carries out branding activities for the people of Surabaya. Reintroduce the public that the city of Surabaya has natural tourist attractions, which can be visited either with family or with friends. This community service activity was carried out by Citivity Academy lecturers from communication science and visual communication design together with students. In the activities carried out to introduce the Surabaya Wonorejo mangrove botanical garden tourism by creating video content which was uploaded on social media. The aim of creating this video content is to promote Surabaya mangrove tourism to the public. When creating video content, it promotes what facilities are available there, apart from providing alternative entertainment venues that are comfortable, cheap and close by. The video content was acted out by students, as an invitation to teenagers to take a nature holiday at the Surabaya Wonorejo mangrove botanical garden.